Aggregation of Human Mesenchymal Stromal Cells Eliminates Their Ability to Suppress Human T Cells - Burand, Anthony J.; Di, Lin; Boland, Lauren K.; Boyt, Devlin T.; Schrodt, Michael V.; Santillan, Donna A.; Ankrum, James A. (Frontiers in Immunology, 2020)
Mesenchymal stromal cells (MSCs) are administered locally to treat sites of inflammation. Local delivery is known to cause MSCs to aggregate into ‘spheroids’, which alters gene expression and phenotype. While adherent MSCs are highly efficient in their inhibition of T-cells, whether or not this property is altered upon MSC aggregation has not been thoroughly determined. In this study, we discovered that aggregation of MSCs into spheroids causes them to lose their T cell suppressive abilities. Interestingly, adding budesonide, a topical glucocorticoid steroid, alongside spheroids partially restored MSC suppression of T cell proliferation. Through a series of inhibition and add-back studies we determined budesonide acts synergistically with spheroid MSC produced PGE2 to suppress T cell proliferation through the PGE2 receptors, EP2 and EP4. These findings highlight critical differences between adherent and spheroid MSC interactions with human immune cells that have significant translational consequences. In addition, we uncovered a mechanism through which spheroid MSC suppression of T cells can be partly restored. By understanding the phenotypic changes that occur upon MSC aggregation and the impact of MSC:drug interactions, improved immunosuppressive MSC therapies for localized delivery can be designed.